2014
DOI: 10.1002/ijc.28819
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZFX confers self-renewal and chemoresistance properties in hepatocellular carcinoma

Abstract: Zinc finger protein X-linked (ZFX) is a zinc finger protein of Zfy family, which is highly conserved in vertebrates. This transcriptional regulator is not only highly expressed in embryonic stem cells (ESC) and hematopoietic stem cells, but is also upregulated in a number of human cancers where it is functional related to cell proliferation and survival. Hepatocellular carcinoma (HCC) is highly aggressive cancer that commonly resistant to most chemotherapies and displays stemness characteristics. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…Overexpression of ZFX contributes to the 'stemness' and pluripotent behavior of cancers. 49,50 Our study further demonstrates that CTCL lesional skin and patient-derived cell lines express other pluripotency ESC markers including CNOT3, KLF4, TBX3, and TRRAP. Detailed description of these genes and their biological activities is provided in Table S1.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Overexpression of ZFX contributes to the 'stemness' and pluripotent behavior of cancers. 49,50 Our study further demonstrates that CTCL lesional skin and patient-derived cell lines express other pluripotency ESC markers including CNOT3, KLF4, TBX3, and TRRAP. Detailed description of these genes and their biological activities is provided in Table S1.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, consistent with the above findings, upstream and downstream members of NANOG signaling are also expressed in CTCL. ZFX (Zinc finger protein Xlinked), a transcription factor, is known to transactivate the promoters of NANOG and SOX2, 49,50 while DAX1 (also known as NR0B1) and MTF2 pluripotency markers are induced by NANOG. 39 All of the aforementioned genes are heterogeneously expressed in CTCL lesional skin.…”
Section: Discussionmentioning
confidence: 99%
“…ZFX could also transactivate c-Myc and the MHC class I HLA-A11 promoters in glioma stem cells (GSCs) and Leydig cells [28,29]. Besides, ZFX has been found to be overexpressed in several solid cancers, including breast cancer [30], prostate cancer [31], Acute T-Lymphoblastic and Myeloid Leukemia [32], hepatocellular carcinoma [33] and non-small cell lung carcinoma [34]. Revelation of ZFX-mediated transactivation of SET provides one mechanism by which ZFX may be implicated in multiple cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Transwell cell invasion assays were performed using Boyden chambers with filter inserts (pore size, 8 µm) coated with 40 µg Matrigel in 24-well plates. Twenty-four hours after transfection with or without siRNA, cells were harvested, and 100 µl serum-free media containing 2x10 5 cells was added into the upper chamber, while 600 µl medium with 20% fetal bovine serum was placed in the lower chamber. Following incubation for 24 h, the cells were fixed in 4% formaldehyde and stained with 0.1% crystal violet in PBS for 30 min at room temperature.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Previous studies have demonstrated elevated levels of ZFX in pluripotent embryonic and hematopoietic stem cells, which is required for self-renewal ability (3,4). Overexpression of ZFX has also been demonstrated to confer self-renewal capability in hepatocellular carcinoma (5). In addition, previous studies have revealed that ZFX plays a notable role in regulating the transcription of genes necessary for cell proliferation, cell cycle and cell death (6,7).…”
Section: Introductionmentioning
confidence: 99%